Enemies within : the culture of conspiracy in modern America - Goldberg, Robert Alan, 1949- (Yale University Press, 2001)
From the Roswell UFO incident to the Communist threat to the rise of the Antichrist, there has been a hunger for conspiracy in America since World War II. Goldberg focuses on five major conspiracy theories of the past half century and examines why they became so popular.